THE IMPLEMENTATION OF CIRC IN IMPROVING STUDENTS’ WRITING SKILL - Sari Wulandari; Sriati Usman; Budi Budi (e-Journal of ELTS (English Language Teaching Society), 2022)
The purpose of this research is to know whether the implementation of CIRC in improving writing skill of the eight grade students of SMP Negeri 4 Palu. The researcher applied quasi experimental research design. The purposive sampling technique was selected in this research to draw the sample. The samples were VIII Manggis as the experimental group and VIII Cempedak as the control group were the number of students were 35. The test which question form was used as the instrument in gathering the data. The data gathered were analyzed statically. The pretest was given to experimental and control group before the treatments were given. After that, the experimental group got the treatment while the control group did not receive any treatment.the posttest was given to both groups. The pretest mean score of the experimental group 39,34 and the control group was 51.08. while,the posttest mean score of the experimental group was 79,78 and the control group was 71,03. After analyzing the data,it is found out that the t-counted value (2,04) was greater than t-table value (1,01) by applying 0,05 level of significance and 30 degree of freedom(df). Based on the result of the research, it is concluded that the hypothesis is accepted. It means, that the implantation of CIRC technique can improve students writing skill at SMP Negeri 4 Palu.